Pseudolaguvia spicula, a new sisorid catfish (Teleostei: Sisoridae) from Bangladesh and northeastern India - Ng, Heok Hee; _, Lalramliana (Zootaxa, 2010)
This study describes Pseudolaguvia spicula, a new miniature sisorid catfish from the Surma-Meghna River system in India and Bangladesh. Pseudolaguvia spicula can be distinguished from congeners in having a combination of: head width 19.2–22.6% SL, dorsal-fin spine length 11.6–14.3% SL, length of dorsal-fin base 13.2–15.9% SL, pectoral-fin spine length 15.7–17.4% SL, length of adipose-fin base 14.7–17.1% SL, pelvic-fin length 14.6–17.1% SL, body depth at anus 12.8–16.8% SL, caudal peduncle length 15.4–17.9% SL, caudal peduncle depth 7.9–9.6% SL, caudal-fin length 24.2–27.5% SL, snout length 48.6–51.9% HL, eye diameter 10.6–13.9% HL, 30–32 vertebrae, smooth anterior edge of dorsal-fin spine, thoracic adhesive apparatus reaching beyond base of last pectoral-fin ray, absence of pale y-shaped marking on dorsal surface of head and supraoccipital process, and indistinct, pale vertical bands on body.